Self-regulated learning as the enabling environment to enhance outcome-based education of undergraduate engineering mathematics - Abdul Rahman, Roselainy (IGI Global, 2014)
The paper discusses the results of an action research to improve teaching practice which applied the philosophy of Knowledge – Experiential – Self-regulated (KES) at the Malaysia-Japan International Institute of Technology, Universiti Teknologi Malaysia. The teaching and learning strategies were implemented to achieve the following objectives; (i) to enhance students' mathematical competencies; (ii) to support self-regulated learning; and (iii) to improve the teaching practice of Engineering Mathematics 3 i.e. Advanced Calculus. A modification to a previously developed framework by Roselainy et al. (2012a) was performed to encourage students to adopt self-regulated learning behaviour in an active learning environment. The teaching, learning and assessment activities were aligned constructively based on the theory of Biggs & Tang (2010). Data was collected, analysed and later employed to modify the teaching and learning activities. The findings found that it is imperative for teachers to design an appropriate learning environment and apply suitable strategies in encouraging and supporting students to embrace and take charge of their own learning.